Efficacy of low molecular weight hyaluronic acid (500–730 kDa) in post-traumatic pathology of periarticular soft tissues at different sites: data from an open-label pilot clinical study - V. A. Nesterenko; M. A. Makarov; A. E. Karateev; E. I. Bialik; V. E. Bialik; A. A. Bialik (Современная ревматология, 2024)
Local injection therapy (LIT) with hyaluronic acid (HA) medications is one of the most promising methods for the treatment of periarticular soft tissue pathology (PASTP) caused by injury or overuse.   Objective: to evaluate the efficacy and safety of LIT with HA medication with a molecular weight of 500–730 kDa in patients with various post-traumatic PASTP.   Material and methods. The study included 30 patients with rotator cuff syndrome (RCS), lateral epicondylitis (LE) and plantar fasciitis (PF) after trauma. Inclusion criteria were the presence of moderate/severe pain (≥40 mm on a visual analogue scale (VAS)) over a 3-month period and the absence of effect of LIT with glucocorticoids. All patients were administered HA peritendinously three times (7 days apart) under ultrasound guidance. Treatment results were evaluated after 1 and 3 months based on the dynamics of pain intensity (VAS) and functional indicators using the ASES (American Shoulder and Elbow Surgical Evaluation), MES (Mayo Elbow Score) and FFI (Foot Functional Index) questionnaires.   Results and discussion. In the general group, there was a statistically significant decrease in pain intensity after 1 and 3 months from a mean of 57.6 ± 14.7 to 37.0 ± 14.8 and 35.0 ± 14.3 mm according to VAS respectively (p < 0.05). In the patient groups with different PASTP, the average assessment of pain intensity and functional impairment at baseline and after 1 and 3 months was: for RCS (n = 11) 59.0 ± 15.1, 39.0 ± 15.7, 36.3 ± 16.2 mm according to VAS and 49.1 ± 14.3, 60.1 ± 13.7, 61.7 ± 3.8 according to ASES, respectively; with LE (n = 10) 54.0 ± 13.4, 35.0 ± 9.7, 34.0 ± 11.7 mm according to VAS and 71.5 ± 11.1, 78.3 ± 9.0, 81.5 ± 8.3 according to MES; with PF (n = 9) 61.0 ± 16.5, 36.6 ± 19.3, 34.4 ± 15.8 mm according to VAS and 47.2 ± 22.8, 39.6 ± 39.7, 39.0 ± 29.9 according to FFI. None of the patients experienced any adverse events during treatment.   Conclusion. HA medication with a molecular weight of 500–730 kDa showed good efficacy and safety in LIT of PASTP of the shoulder, elbow joint and foot. Further studies are needed to evaluate the possibility of a broad use of the drug for the treatment of PASTP in real clinical practice.